Adaptation of medical laboratory scientists to workplace hazards - experiences from the COVID-19 pandemic - Blanka Wolszczak-Biedrzycka; Anna Bieńkowska; Stanisław Maksymowicz (Frontiers Media S.A., 2022)
The COVID-19 pandemic has dramatically changed healthcare personnel's working environment and sense of security. Medical laboratory scientists were also faced with new occupational challenges. They were tasked with performing novel tests for SARS-CoV-2 without being aware of the associated risks. At the beginning of the pandemic, strict sanitary requirements and the fear of becoming infected with the "new virus" were considerable sources of stress. However, these stress responses abated over time. The aim of this two-stage study was to explore the extent to which this group of medical professionals adapted to new working conditions 1 year after the outbreak of the pandemic. The study was conducted at the beginning of the fourth pandemic wave in Poland, i.e., between 10 September and 31 October 2021. The first stage was a pilot study that involved interviews with 14 medical laboratory scientists. The results were used to perform a survey of 294 laboratory scientists in the second stage. The study investigated the problems and fears faced by this professional group at the beginning of the pandemic, as well as changes in their attitudes during successive waves of COVID-19. The analyzed data demonstrated that most medical laboratory scientists had grown accustomed to the pandemic and workplace changes by the beginning of the fourth wave. The study also indicates that in addition to adequate means of personal protection, health professionals should also be provided with emotional support in times of pandemic.